PERAN GANDA PEREMPUAN PEMULUNG ETNIS BATAK DI TEMPAT PEMBUANGAN AKHIR MUARA FAJAR KECAMATAN RUMBAI PEKANBARU - ", Christian; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Muara Fajar Landfills in Rumbai, subdistrict area of Pekanbaru city with such problem (1) what are the dual role of Batak ethnic scavengers woman in carrying out family functions?, (2) what are impact of the dual role of Batak ethnic scavengers woman toward their families?. This study aims to determine the role of Batak ethnic scavengers in carrying out family functions and impacts. The research method used was desciptive quantitive. The sample of this study were women of Batak ethnic who work as scavengers in Muara Fajar Landfills, have husband, childrens and livestock of pigs in Rumbai, subdistrict of Pekanbaru city. Total numbers of samples at this research were 30 respondents. Researcher used quesioner and documentation to collect data. Based on this research there are seven function of family carried out by Batak ethnic scavengers woman toward family such as education, socialisation, protectness, feeling, economy, recreative and biological function. 23 respondent (77%) carried out family function while 7 respondent (23%) were not. Impact of dual role of Batak ethnic scavengers woman toward family such make independent and responsable of childrens, achievement, education charge, help husband and increased of family economy power. 27 respondent (90%) are agreed that dual role result positive impact towrad family, rest 3 respodent (10%) were not. Negative impact from dual role of Batak ethnic scavengers woman such denied education of childrens, mother get angry to childrens, mother get stress, limited of quality time and wife are not respectfull to husband. 17 respondent (57%) are agreed dual role of Batak ethnic scavengers woman toward family resulted negative impact while 13 respondent (43%) were not agreed dual role of Batak ethnic scavengers woman result negative impact toward family. Keywords : Dual Roles, Scavengers Woman, Function Of Family.